Collective bargaining systems and macroeconomic and microeconomic flexibility: The quest for appropriate institutional forms in advanced economies - John T. Addison (IZA Journal of Labor Policy, 2016)
This paper addresses the design of the machinery of collective bargaining from the perspective of microeconomic and macroeconomic flexibility. In the former context, somewhat greater attention is given over to enterprise flexibility than external adjustment. In the latter context, close attention is also paid to changes in collective bargaining along the dimensions of bargaining coverage, structure, and coordination. Support is adduced for the German, contemporary Scandinavian, and British models. The role of trust in securing micro and macro flexibility also receives attention, suggesting that the polder or Dutch model might also be expected to populate the firmament of fit-for-purpose collective bargaining arrangements.
Keywords: D02; E02; E24; E25; E61; J08; J51; J52; J53; J58; P51; 330; Bargaining coverage/structure/coordination; Collective bargaining; Decentralization; Growth; Inequality; Micro/macro flexibility; Pacts; Social pacts; Stabilization; Trust; Unemployment; Voice